2022
DOI: 10.1002/mma.8688
|View full text |Cite
|
Sign up to set email alerts
|

An exponential stabilization of random impulsive control systems and its application to chaotic systems

Abstract: This paper addresses the problem of pth moment exponential stability and stabilization for random impulsive control systems. Some novel pth moment exponential stability and synchronization approaches are established based on the method of maximum and minimum eigenvalues by using the Lyapunov functions and Razumukhin technique. Finally, we show that the stability and synchronization behavior of random impulses are faster than the fixed time impulses. Some physical examples are given to verify the validity and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In previous studies [31][32][33], the stochastic time delay systems with random impulsive effects were studied. Recently, previous works [34,35] discussed the robust mean square stability for linear and nonlinear uncertain systems under RIC, and in the literature [36,37], the authors showed RIC provides faster convergence time. To the best of our surveillance, there is no paper that analyses the stability results of random impulsive control USTDSs and the question about the stability analysis for random impulsive control USTDSs remains untouched so far.…”
mentioning
confidence: 99%
“…In previous studies [31][32][33], the stochastic time delay systems with random impulsive effects were studied. Recently, previous works [34,35] discussed the robust mean square stability for linear and nonlinear uncertain systems under RIC, and in the literature [36,37], the authors showed RIC provides faster convergence time. To the best of our surveillance, there is no paper that analyses the stability results of random impulsive control USTDSs and the question about the stability analysis for random impulsive control USTDSs remains untouched so far.…”
mentioning
confidence: 99%